"It's Not the Shunt": An Algorithm for the Assessment of Other Medically Actionable Causes of Vomiting in Children With Craniofacial Malformations. (July 2019) - Maxey, Dawn; Lee, Amy; Wenger, Tara
Background: After shunt malfunction has been ruled out in children with craniofacial malformations with vomiting, it can be challenging to effectively communicate with front-line providers about their unique medically actionable causes of vomiting as compared to children whose shunts were placed for other reasons (eg, prematurity/intraventricular hemorrhage). Solution: An algorithm to facilitate communication "What we did that is new": We developed an algorithm to facilitate communication regarding emergent evaluation of vomiting in this population.